Natural Nitrogenous Sesquiterpenoids and Their Bioactivity: A Review - De-Li Chen; Bo-Wen Wang; Zhao-Cui Sun; Jun-Shan Yang; Xu-Dong Xu; Guo-Xu Ma (Molecules, 2020)
Nitrogenous sesquiterpenoids fromnatural sourcesare rare, so unsurprisingly neither the potentially valuable bioactivity nor thebroad structural diversity of nitrogenous sesquiterpenoids has been reviewed before. This report covers the progressduring the decade from 2010 to February 2020 on the isolation, identification, and bioactivity of 391 nitrogen-containing natural sesquiterpenes from terrestrial plant, marine organisms, and microorganisms. This complete and in-depth reviewshouldbe helpful for discovering and developing new drugs of medicinal valuerelated to natural nitrogenous sesquiterpenoids.